Increasing the Energy Efficiency of Traction Electric Drives of Direct Current - Kovalov, V. M.; Kovalova, Yu. V. (Science and Transport Progress, 2024)
Purpose. The work is aimed at improving the energy efficiency of direct current traction electric drives of electric transport by introducing transistor pulse width converters (PWC) with an optimal switching frequency to minimize total electrical losses in the electric drive. The electrical losses of traction electric drives consist of electrical losses in the armature winding and in the PWC transistors. Methodology. To study the dependence on the switching frequency of transistors, the electrical losses in the armature winding and PWC transistors are divided into two parts: static losses from the direct current component of the current and dynamic losses, i.e., losses in the armature winding from harmonic current components and losses in the transistors from transient switching currents. Since the dynamic electrical losses in transistors increase with increasing frequency and decrease in the armature winding, it is necessary to find the optimal PWC co-mutation frequency at which the total dynamic losses in the traction electric drive will be minimal. The goal of increasing energy efficiency in a traction electric drive is achieved by determining the dependence of dynamic electrical losses in the armature winding on the switching frequency of the PWC and computer modeling of the transistor electric drive. Findings. It is found that the relative dynamic electrical losses in the armature winding in the case of polyharmonic power supply are equal to the square of the armature current ripple coefficient. An algorithm for determining the optimal switching frequency of the PWC is developed: 1) the dependence of dynamic electrical losses on the switching frequency of transistors is determined experimentally on computer models of the motor and PWC; 2) the graph of the dependence of total dynamic electrical losses of the transistor electric drive on the time-tothe point of minimum losses, which corresponds to the optimal frequency value, is determined. Originality. For the first time, the authors obtained an analytical expression for the relative dynamic electrical losses in the armature windings, which are equal to the square of the armature current ripple factor. Practical value. Establishing the optimal switching frequency of the PWC according to the developed methodology reduces electrical losses in traction electric drives, i.e., increases their energy efficiency.